Tracing the Base: A Topographic Test for Collusive Basing-Point Pricing - Iwan Bos; Maarten Pieter Schinkel (Tinbergen Institute, 2009)
Basing-point pricing is known to have been abused by geographically dispersed firms in order to eliminate competition on transportation costs. This paper develops a topographic test for collusive basing-point pricing. The method uses transaction data (prices, quantities) and customer project site locations to recover the basing-point(s) from which delivered prices were calculated. These bases are compared to the locations of the production mills in a test that discriminates between competitive and collusive basing-point pricing. We define a measure for the likelihood of collusion that can be used to screen industries that traditionally apply delivered pricing for the presence of cartels. We operationalize this screen with a software. The test is hard to beat for cartels using this otherwise elusive form of price-fixing. When a cartel was found to have abused the basing-point system, our method can be used to estimate antitrust damages.
Keywords: L41; K42; C12; 330; basing-point pricing; cartels; detection; antitrust; damages; Räumlicher Wettbewerb; Preismanagement; Kartell; Makroökonomischer Einfluss; Kartellrecht; Rechtsdurchsetzung; Theorie